First-Grade Reading Instruction and Reading Growth: Asian Language Minorities and Native-English-Speaking Peers - Melody Kung (SAGE Publishing, 2019)
The present study explores whether the relation between aspects of first-grade reading instruction and reading growth through eighth grade differed for Asian language minority (LM) children and native-English-speaking (NE) children. The sample consisted of 6,715 NEs and 242 Asian LMs, followed from first to eighth grade. Findings were as follows: (a) The relation between first-grade sounds/letters instruction and reading growth slightly differed for Asian LMs and NEs. For example, Asian LMs who received more sounds/letters instructional emphasis decelerated less through middle grades, and by eighth grade, performed on par with NEs. (b) The relation between first-grade meaning instructional emphasis and reading growth did not differ for the two groups. (c) NEs experienced more deceleration through middle grades. Implications and future directions are discussed.